Influence of nano-hydroxyapatite on mechanical behavior of microwave processed polycaprolactone composite foams. (12th June 2019) - Verma, Nishant; Zafar, Sunny; Talha, Mohammad
Abstract: Present work is focused towards manufacturing of nano-hydroxyapatite (nHA) reinforced polycaprolactone (PCL) composite foams by microwave processing route. The nHA of size approximately 100 nm was used as reinforcement in the range of 5 to 20 wt% along with neat PCL. To generate interconnected pores, salt (NaCl) leaching was performed in an ultrasonicator bath for 1 week. The mechanical behavior of the nHA-PCL foams was assessed in terms of tensile, flexural, hardness and Izod impact tests. The glass transition (Tg ) temperature of microwave processed nHA-PCL foams was observed using thermogravimetry analysis (TGA). The porosity and interconnectivity in the foam specimens were assessed using image analysis and density measurements. The pore size was obtained in the range of 98–285 μ m. The porosity in the microwave processed nHA-PCL foams was in the range of 68%–72% with the interconnectivity of 30%–40%. It was observed that the tensile, hardness, flexural strength with 20 wt% of nHA was 145.90%, 52%, 96% more than neat PCL foam. The impact strength with 20 wt% of nHA was 60% less than neat PCL foam.